2011
DOI: 10.5140/jass.2011.28.1.079
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Operation Mechanism of Ongnu, the Astronomical Clock in Sejong Era

Abstract: Ongnu (Jade Clepsydra; also called Heumgyeonggaknu) is a water clock was made by Jang Yeong-sil in 1438. It is not only an automatic water clock that makes the sound at every hour on the hour by striking bell, drum and gong, but also an astronomical clock that shows the sun's movement over time. Ongnu's power mechanism used is a water-hammering method applied to automatic time-signal device. The appearance of Ongnu is modeled by Gasan (pasted-paper imitation mountain) and Binpungdo (landscape of farming work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…8 The fixed quantity supply of water and constant speed operating of the water wheel is most important to the waterhammering type water clock. Kim et al (2011) suggested that a fixed quantity water in Uigi (欹器, inclining vessel) which is supplied from southern Gwanin (官人, government official)'s golden bottle spilled into Nusudae as time passed and this water move into a small vessel which is hanging from the water wheel in Heumgyeonggaknu and then this water-filled device is operating Cheonhyeong system (天衡, oriental escapement device).…”
Section: Structure and Water-hammering Methods Of Heumgyeonggaknumentioning
confidence: 99%
See 2 more Smart Citations
“…8 The fixed quantity supply of water and constant speed operating of the water wheel is most important to the waterhammering type water clock. Kim et al (2011) suggested that a fixed quantity water in Uigi (欹器, inclining vessel) which is supplied from southern Gwanin (官人, government official)'s golden bottle spilled into Nusudae as time passed and this water move into a small vessel which is hanging from the water wheel in Heumgyeonggaknu and then this water-filled device is operating Cheonhyeong system (天衡, oriental escapement device).…”
Section: Structure and Water-hammering Methods Of Heumgyeonggaknumentioning
confidence: 99%
“…1 was made so that every puppet is standing up. 9 For the study of Kim et al (2011), it is hard to be regarded as the key device related with water-hammering type control considering that the Uigi is installed separately as stated in the literature record (Myeongjong Sillok 10:92a:10 ~ 14). (Myeongjong Sillok 10:92a:10 ~ 14; 領觀象監事李芑啓曰 前者, 以欽敬閣欹器, 虛而不欹, 故今改造而進.…”
Section: Structure and Water-hammering Methods Of Heumgyeonggaknumentioning
confidence: 99%
See 1 more Smart Citation
“…Shui yün i hsiang t'ai of 11th century and Borugaknu of 15th century had such a function. Kim et al (2011) and Lee & Kim (2012) presumed that the overflow method was also applied to Heumgyeonggaknu and the water-hammering type celestial globe. The generation and control of the driving force using the alarm clock Tongcheonui, which is another instrument in the Nongsugak, the personal observatory of Hong Dae-Yong, is by a weight and a foliot type escapement system.…”
Section: Concept Design Of Honsanguimentioning
confidence: 99%